Caracterização petrográfica, mineraloquímica e geoquímica de rochas metassedimentares do grupo Macururé do nordeste de Sergipe - Santos, Victor Menezes (2023)
The Macururé Group (GM) in the state of Sergipe is part of the Macururé Domain and is the largest representative of this unit, accounting for around 80% of the volume of outcropping rocks. This work aimed to study the metasedimentary rocks of the GM in the northeastern part of the state. The rocks studied were classified as: metapelite, metarhythmite and metagraywaeke. They are very fine to fine grained (<1.5 mm), gray to greenish in color, preserve primary structures (e.g. depositional bedding and rhythmic structures), and have a lepidoblastic and porphyroblastic texture. The essential mineralogy of this group of rocks is made up of muscovite, quartz, biotite and plagioclase, and the accessory mineralogy is made up of: opaque minerals, zircon, apatite, chlorite, epidote, bastnaesite and monazite. The specific mineral chemistry analyses of the metasedimentary rocks enabled the minerals to be named: plagioclase corresponds to the members albite and oligoclase; brown mica was defined as Fe-biotite and Mg-biotite; white mica was classified as muscovite and fengite, garnet shows that the porphyroblasts are more enriched with almandine molecules, with a lower content of pyrope, grossular and spersartite, respectively. Pressure and temperature estimates were based on the titanium content in biotite. The pressures ranged from 3.34 Gpa (core) to 3.7 Gpa (rim) and the temperatures obtained ranged from 392 to 671°C.The geochemical analyses of the whole rock show that incipient weathering in the formation process of these rocks can be related to high levels of Al2O3, CaO, K2O and Na2O. The samples show large variations in the LILEs: Rb (49.3-150.5 ppm), Sr (52.2-557 ppm) and La (15.6-55.2 ppm) and little variation in the HFSEs Nb (8.1-16.9 ppm) and Ta (0.6-1 ppm). The geochemical signatures indicate sources from intermediate igneous rocks and immature sediments from magmatic arcs and oceanic islands.